The Influence of Islamic Education Values in Strengthening Tolerance in a Multicultural Society - Adytiya, Adytiya; Noviani, Dwi; Paizaluddin, Paizaluddin; Laksita, Andrini Lita (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This research aims to analyze the role of Islamic educational values, namely rahmah (compassion), ukhuwah (brotherhood), and adl (justice), in strengthening attitudes of tolerance among madrasa and Islamic-based school students in Ogan Ilir Regency, South Sumatra. A quantitative approach was used in this research involving 300 students as samples. Data was collected through questionnaires tested for validity and reliability, and analyzed using descriptive statistics and simple linear regression. The results of the research show that the values of rahmah, ukhuwah, and adl have a significant effect on students' tolerance attitudes, with a coefficient of determination (R²) of 48%, which means that 48% of the variation in students' tolerance attitudes can be explained by the application of these values. The value of mercy has the greatest contribution in forming an attitude of tolerance, followed by ukhuwah and adl. However, challenges such as a lack of understanding of pluralism and a less than dialogical teaching approach are still obstacles in optimizing educational tolerance. This research concludes that Islamic education, through applying the values of mercy, ukhuwah, and adal, has great potential in forming a tolerant generation. Therefore, it is recommended that a more inclusive curriculum be developed, teacher training in teaching pluralism strengthened, and collaboration between Islamic and general education institutions increased.